ACTonDiabetes: study protocol of a pragmatic randomised controlled trial for the evaluation of an acceptance and commitment-based internet-based and mobile-based intervention for adults living with type 1 or type 2 diabetes. Issue 9 (15th September 2022) - Bendig, Eileen; Schmitt, Andreas; Wittenberg, Amelie; Kulzer, Bernhard; Hermanns, Norbert; Moshagen, Morten; Baumeister, Harald
Abstract : Introduction: Living with diabetes can be burdensome and lead to serious emotional distress and impaired mental health. Acceptance and commitment therapy (ACT) can support people facing the challenges of living with diabetes. This trial aims to evaluate the effectiveness and cost-effectiveness of the internet-based and mobile-based intervention (IMI) 'ACTonDiabetes' in reducing diabetes distress against enhanced treatment as usual (TAU+) following specialised diabetes care. Methods and analysis: A two-armed pragmatic randomised controlled trial will be conducted to evaluate the guided IMI ACTonDiabetes against TAU+. A total of 210 adults with type 1 or type 2 diabetes and elevated diabetes distress (Problem Areas in Diabetes ≥40) will be recruited at a specialised diabetes centre. The intervention begins 2–4 weeks after hospital discharge and takes about 7–10 weeks to complete. Assessments are performed at baseline and 5 and 10 weeks as well as 6 and 12 months after randomisation. The primary outcome is diabetes distress at a 10-week follow-up (T2). Secondary outcomes are depression (Patient Health Questionnaire-8), psychological well-being (WHO-5), quality of life (Assessment of Quality of Life-8 Dimension), Diabetes-related Self-Management Questionnaire, diabetes acceptance (Acceptance and Action Diabetes Questionnaire) and negative treatment effects (Inventory for the Assessment of Negative Effects of Psychotherapy). All statistical analyses will be performed based on the intention-to-treat principle with additional per-protocol analyses. Changes in outcomes will be evaluated using the general linear model. A health-economic evaluation will be conducted from a societal perspective. Reasons for drop-out will be systematically investigated. Ethics and dissemination: This clinical trial has been approved by the State Medical Chamber of Baden-Württemberg (file no. B-F-2019-010). Trial results will be submitted for publication in a peer-reviewed journal and presented at conferences. Trial registration number: DRKS00016738.